2020
DOI: 10.1097/meg.0000000000001499
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious effect of proton pump inhibitors on the disease course of cirrhosis

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NCND), where it is permissible to download and share the work provided it is properly cited. The work cannot be changed in any way or used commercially without permission from the journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 45 publications
(64 reference statements)
1
23
1
Order By: Relevance
“…Among the 12 patients in the PH group, 11 were taking proton pump inhibitors (PPIs), so the relationship between the ongoing use of PPIs for the treatment of varices was also taken into consideration (12)(13)(14)(15). It has been reported that the partial changes in the gut microbiota caused by PPI usage are similar to the changes caused by the progression of liver cirrhosis, and increased inflow of oral flora to the intestines might create an intestinal environment that is a risk factor for the progression of liver cirrhosis, spontaneous bacterial peritonitis, and hepatic encephalopathy (9,(16)(17)(18)(19). The levels of genera (Lactobacillales, Streptococcus, Selenomonas, Veillonella, Campylobacter, and Haemophilus) have been reported to be high in PPI users (20).…”
Section: Discussionmentioning
confidence: 99%
“…Among the 12 patients in the PH group, 11 were taking proton pump inhibitors (PPIs), so the relationship between the ongoing use of PPIs for the treatment of varices was also taken into consideration (12)(13)(14)(15). It has been reported that the partial changes in the gut microbiota caused by PPI usage are similar to the changes caused by the progression of liver cirrhosis, and increased inflow of oral flora to the intestines might create an intestinal environment that is a risk factor for the progression of liver cirrhosis, spontaneous bacterial peritonitis, and hepatic encephalopathy (9,(16)(17)(18)(19). The levels of genera (Lactobacillales, Streptococcus, Selenomonas, Veillonella, Campylobacter, and Haemophilus) have been reported to be high in PPI users (20).…”
Section: Discussionmentioning
confidence: 99%
“…An early meta-analysis published in 2015 showed that PPI use was not associated with increased mortality in patients with cirrhosis [11]. However, only four cohort studies [14,16,17,19] were included in the present study, and many related cohort studies have been published since the previous meta-analysis [18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. In addition, it remains unknown…”
Section: Introductionmentioning
confidence: 89%
“…Overall, 21 cohort studies with 20,899 patients and 7457 death events were included, of which 16 were retrospective cohort studies [16][17][18][19][22][23][24][25][26][27][28][29][30][31][32][33], while the other five were prospective cohort [14,15,20,21,34]. As for the ethnicity of the patients, 12 studies included Caucasian patients [15,16,18,[20][21][22]24,28,29,[32][33][34], 7 included Asians [17,19,23,25,26,30,31], and the remaining 2 included patients with mixed ethnicity [14,27]. Most of the studies included patients with hospitalized patients with cirrhosis without serious clinical complications [14][15][16][17][18]…”
Section: Study Characteristics and Quality Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…A 5-year follow-up observational study assessed the impact of long-standing PPI use on outcomes in a cohort of 350 cirrhotic patients, divided between regular PPI users (n = 196) and non-users (n = 154) [56]. Regular PPI use was associated with an increased cumulative probability of developing SBP compared to non-users [55% vs. 24.8%, hazard ratio (HR) 4.25; p = 0.05].…”
Section: Proton Pump Inhibitors (Ppis)mentioning
confidence: 99%